Fine structure in electronic transitions attributed to nitrogen donor in silicon carbide - Assmann, Nicole; Persson, Clas; Kuznetsov, A. Yu; Monakhov, Eduard V. (Applied physics letters, 2021)
Nitrogen in group-IV semiconductors has become a well-established element of qubits capable of room-temperature operation. In silicon carbide, nitrogen can occupy different nonequivalent lattice sites, giving rise to different shallow donor states. We report a triplet fine structure in electronic transitions of nitrogen donors on the quasi-cubic carbon site in 4H silicon carbide with activation enthalpies of around 100 meV. The intensities of triplet components have a prominent dependence on the voltage bias. The activation enthalpies of the transitions exhibit the Poole-Frenkel effect, while no bias dependence is observed for the magnitude of splitting. A tentative explanation of the fine structure involves local symmetry changes due to stacking faults.